Association of anticholinergic medications and AD biomarkers with incidence of MCI among cognitively normal older adults. (20th October 2020) - Weigand, Alexandra J.; Bondi, Mark W.; Thomas, Kelsey R.; Campbell, Noll L.; Galasko, Douglas R.; Salmon, David P.; Sewell, Daniel; Brewer, James B.; Feldman, Howard H.; Delano-Wood, Lisa
Abstract : Objective: To determine the cognitive consequences of anticholinergic medications (aCH) in cognitively normal older adults as well as interactive effects of genetic and CSF Alzheimer disease (AD) risk factors. Methods: A total of 688 cognitively normal participants from the Alzheimer's Disease Neuroimaging Initiative were evaluated (mean age 73.5 years, 49.6% female). Cox regression examined risk of progression to mild cognitive impairment (MCI) over a 10-year period and linear mixed effects models examined 3-year rates of decline in memory, executive function, and language as a function of aCH. Interactions with APOE ε4 genotype and CSF biomarker evidence of AD pathology were also assessed. Results: aCH+ participants had increased risk of progression to MCI (hazard ratio [HR] 1.47, p = 0.02), and there was a significant aCH × AD risk interaction such that aCH+/ε4+ individuals showed greater than 2-fold increased risk (HR 2.69, p < 0.001) for incident MCI relative to aCH−/ε4−), while aCH+/CSF+) individuals demonstrated greater than 4-fold (HR 4.89, p < 0.001) increased risk relative to aCH−/CSF−. Linear mixed effects models revealed that aCH predicted a steeper slope of decline in memory ( t = −2.35, p = 0.02) and language ( t = −2.35, p = 0.02), with effects exacerbated in individuals with AD risk factors. Conclusions: aCH increased risk of incident MCI and cognitive decline, and effects were significantly enhanced among individuals with genetic risk factors and CSF-based AD pathophysiologic markers. Findings underscore the adverse impact of aCH medications on cognition and the need for deprescribing trials, particularly among individuals with elevated risk for AD.